KEMAMPUAN MENULIS LAMBANG BILANGAN BAHASA INGGRIS MELALUI DIRECT METHOD - Pulukadang, Wiwy T.; Rahmat, Abdul; Rohmawaty, Sity (Ideas Publishing, 2018)
The problem statement in this research is the Student’s Ability in Writing the English numeral sign improved? The aim of the research is to improve the Student’s Ability in Writing the English numeral sign. The method which is used the action research. The data collection collected through the descriptive the instrument used test and observation work sheet. The conclusion was the the Student’s Ability in Writing the English numeral sign can improve.